Implementasi Pembelajaran Kooperatif Kancing Gemercing dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran IPA di Kelas IV MI Al-Ihsan Kayuaru - Nurzaidah; Ruslaini (Journal of Education and Learning Sciences, 2023)
This study aims to analyze and explain the implementation of the kancing gemerincing technique in improving students' learning outcomes in Science at the 4th grade of MI Al-Ihsan Kayuaru. The method used in this study is Classroom Action Research (CAR), conducted in two cycles with 21 students as participants. The kancing gemerincing technique is employed to encourage active student participation in learning through a cooperative method, allowing students to actively participate, express ideas, and listen to each other's opinions in groups. The results of the study show a significant improvement in students' learning outcomes, from 71.4% in the first cycle to 95.2% in the second cycle. The findings indicate that the kancing gemerincing technique successfully increased students' activity in asking questions, expressing ideas, and engaging in practice. The application of this technique was also effective in improving students' understanding of the topics related to heat energy, sound energy, and alternative energy. The kancing gemerincing technique is effective in enhancing students' learning outcomes and activity. This technique can be applied in Science learning for the 4th grade of MI Al-Ihsan Kayuaru and can be extended to other subjects to facilitate positive student interaction and improve the overall quality of learning.